An ecological and population study of the land snail (Candidula gigaxii L.Pfeiffer, 1850) in selected locations in Baghdad province. (Journal of the College of Basic Education, 2022)
أجريت الدراسة الحالية على القوقع الأرضي Candidula The current study was conducted on the ground snail Candidula gigaxii gigaxii في مواقع مختارة من محافظة بغداد, وتم خلال هذه الدراسة جمع الأفراد الحية والأصداف الفارغة للنوع C. gigaxii من أربعة مواقع للدراسة شملت مواقع الجادرية والزعفرانية وصدر القناة والتاجي وبواقع خمسة مكررات ذات متر مربع واحد شهريا للفترة الممتدة من حزيران 2013 ولغاية آيار 2014 , وتضمنت الدراسة حساب دليل النمو Ia in selected locations of the province in Baghdad. The collection of live individuals and empty shells of specie C. gigaxii have been conducted for four sites including Jadiriya, Zafaraniyah, Sadir Al-Qanat and Taji and by five replications of one square meter per month for the period from June 2013 until May 2014, and the study included growth account Index Ia لصدفة النوع C. gigaxii for C. gigaxii وعلاقة التغايرات الحاصلة في دليل النمو Ia and the relationship of variations occurring in the growth Index Ia مع بعض الخصائص الفيزيائية والكيميائية كدرجة حرارة الهواء (م ˚ ) ومحتوى التربة من الرطوبة (% ) , وقد أظهرت النتائج لدليل نمو الصدفة Ia with some physical and chemical properties such as the air temperature (m˚) and soil content of moisture (%). The results of growth Indexللأفراد الحية للنوع C. gigaxii أوطأ قيمة سجلت 1.95) ) ملم في شهر شباط 2014 في موقع الزعفرانية وأعلى قيمة بلغت 3.86) ) ملم في شهر تشرين الثاني 2013 في موقع التاجي , في حين سجلت نتائج دليل النمو Ia Ia of the living individuals of the species C. gigaxii showed the lowest value of (1.95) mm in February 2014 in the Zafaraniyah site and the highest value was (3.86) mm in November 2013 in Taji Site, while the results of growth Index Ia ofللأصداف الفارغة للنوع C. gigaxii empty shells of specie C. gigaxii recorded أوطأ قيمة 1.8) ) ملم في شهر آذار 2014 في موقع صدر القناة وأعلى قيمة بلغت 2.65) ) ملم في شهر نيسان في موقع الزعفرانية , وقد أظهرت النتائج إن دليل نمو الصدفة Ia the lowest value of (1.8) mm in March 2014 in Sadir Al-Qanat Site and the highest value reached (2.65) mm in April at the site of Zafaraniyah. The results showed that the shell growth Index Ia قد تأثر بالتغايرات الشهرية والموقعية للعوامل البيئية كدرجة حرارة الهواء (م ˚ ) ومحتوى التربة من الرطوبة (% ) , وتراوحت قيم درجة حرارة الهواء بين 34-10) ) م ˚ في شهري كانون الثاني وتموز 2014 has been influenced by the monthly and location variations of the environmental factors such as air temperature (m˚) and soil moisture content (%), and the values of air temperature ​​ranged between (34-10) m˚ in January and July 2014 in the sites of Sadir Al-Qanat and Jadiriya respectively, while soil moisture content ranged between (9-33)% in May 2014 and December 2013 in Jadiriya and Sadir Al-Qanat Sites respectively. the results have been analyzed by using statistical and standard methods including calculation the value of least significant difference LSD for